2010
DOI: 10.1002/elan.200900615
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Modifying Gold and Carbon Electrode with 4‐Sulfophenyl Diazonium Salt

Abstract: A comparison of the reductive adsorption behavior of 4-sulfophenyl diazonium salt and subsequent electrochemical reactivity on gold relative to carbon was studied with some significant differences observed. The ability of the 4-sulfophenyl layer adsorbed onto gold to block access of the redox probe ferricyanide to the underlying electrodes, as determined via cyclic voltammetry was inferior to the same layers formed on glassy carbon electrodes thus indicating a more open, porous layer formed on gold. More signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
1
38
3
Order By: Relevance
“…The electrochemical reduction of 4-nitrophenyl on glassy carbon has been well studied by Belanger and coworkers [23], and Downard and co-workers [24] which compared reductions by CV in different mediums as well as comparison to the chemical method. The current study is significant as, contrary to other studies performed that show the electrochemical reactivity of aryl diazonium salt derived layers is greater on gold than carbon [15,18], the electrochemical conversion of the 4-nitrophenyl to 4-aminophenyl proceeds more rapidly on carbon than on gold. This observation is rationalized by the unique quinoid structure that nitrobiphenol molecules have been shown to form on carbon surfaces [25,26], to demonstrate why this apparently contradictory observation is in fact consistent with previous observations.…”
Section: Introductioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The electrochemical reduction of 4-nitrophenyl on glassy carbon has been well studied by Belanger and coworkers [23], and Downard and co-workers [24] which compared reductions by CV in different mediums as well as comparison to the chemical method. The current study is significant as, contrary to other studies performed that show the electrochemical reactivity of aryl diazonium salt derived layers is greater on gold than carbon [15,18], the electrochemical conversion of the 4-nitrophenyl to 4-aminophenyl proceeds more rapidly on carbon than on gold. This observation is rationalized by the unique quinoid structure that nitrobiphenol molecules have been shown to form on carbon surfaces [25,26], to demonstrate why this apparently contradictory observation is in fact consistent with previous observations.…”
Section: Introductioncontrasting
confidence: 78%
“…Comparative studies of reductive adsorption of diazonium salts on gold versus glassy carbon have been conducted previously by Gooding and co-workers regarding the electron transfer efficiencies through the resulting 4-carboxylphenyl layers [15], their application in electrochemical sensing [17] and the electrochemical reactivities of 4-sulfophenyl layers [18]. Each of these studies have observed less charge transfer resistance through aryl diazonium salt-derived layers on gold when compared with the equivalent on glassy carbon.…”
Section: Introductionmentioning
confidence: 97%
“…SAMs of alkanethiol, have been only performed on gold electrodes. 17,111,112 It is now generally agreed that depending on the precise experimental conditions used in the self-assembly process (i.e. charge allowed to reduce the diazonium salt, reaction times, concentration of the SAM-forming molecule, nature of the substrate), 98 further radical attack at the first grafted aryl group can yield a polyphenylene layer (i.e.…”
Section: Aryl Diazonium Salt Derived Layersmentioning
confidence: 99%
“…Electrografting in particular has gained tremendous interest over the last decade and is now a well-recognized method for surface functionalization [20][21][22][23][24] . Contrary to alkylthiol SAMs, the organic layers obtained from this method are generally highly stable, being strongly resistant to heat, chemical degradation and ultrasonication 20,25 . Furthermore, the method is easy to process and fast (deposition time on the order of 10 s instead of 10-18 h for well-organized thiol-Au SAMs) and can be applied to a wide range of materials: carbon (graphite, glassy carbon (GC), nanotubes, diamond), metals (Fe, Co, Ni, Cu, Zn, Pt, Au), semiconductor (SiH, SiO 2 , SiOC…), indium tin oxide and even organic polymers and dyes 22 .…”
mentioning
confidence: 99%